We thought you would be prettier eaudiobook True tales of the dorkiest girl alive. - Notaro, Laurie (Tantor Media, 2011)
She thought she'd have more time. Laurie Notaro figured she had at least a few good years yet. But no—it's happened. She has officially lost her marbles. From the kid at the pet-food store checkout line whose coif is so bizarre it makes her seethe "I'm going to kick his hair's ass" to the hapless Sears customer service rep on the receiving end of her Campaign of Terror, no one is safe from Laurie's wrath. Her cranky side seems to have eaten the rest of her—inner-thigh Chub Rub and all. And the results are breathtaking. Her riffs on e-mail spam, eBay ("There should be an eBay wading pool, where you only get to bid on Precious Moments figurines and Avon products, and you have to make it through that first before jumping into the deep end"), and the perils of St. Patrick's Day ("When I'm driving, the last think I need is a herd of inebriates darting in and out of traffic like loaded chickens") are the stuff of legend. And for Laurie, it's all 100 percent true.